Enteroviral rhombencephalitis presenting with ocular flutter. (February 2017) - Fong, Michael; Babu, Sangamithra; Wolfe, Nigel
Highlights: Ocular flutter is characterised by spontaneous bursts of horizontal saccades. Ocular flutter occurs due to failure of omnipause nuclei. Ocular flutter has a broad differential diagnosis, including post-infectious causes. Abstract: Ocular flutter is a dramatic clinical sign that poses multiple diagnostic considerations. The case description outlines a well young male that presented with ocular flutter and truncal ataxia. The clinical syndrome was subsequently attributed to enteroviral rhombencephalitis. The mechanism and neuroanatomical correlates are discussed, and potential treatments considered.